2011
DOI: 10.1038/onc.2011.116
|View full text |Cite
|
Sign up to set email alerts
|

C10ORF97 is a novel tumor-suppressor gene of non-small-cell lung cancer and a functional variant of this gene increases the risk of non-small-cell lung cancer

Abstract: In an earlier study we showed that C10ORF97 (chromosome-10, open reading frame-97) was expressed in almost all of the tissues and cell lines tested, and that it inhibited the growth of seven tumor cell lines, including two lung carcinoma cell lines (A549 and PG). Here, we show that C10ORF97 is downregulated in non-small-cell lung cancer (NSCLC) tissue compared with normal lung tissue. Overexpression of C10ORF97 significantly suppressed human lung carcinoma A549 cell growth (proliferation and anchorage-independ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 32 publications
1
11
0
Order By: Relevance
“…Recently, we have pointed out that the expression of CARP is significantly decreased in lung cancer tissues, suggesting that decreased expression of CARP might be associated with tumorigenesis of lung cancer [10]. In the present study, a similar tendency in the change of CARP expression was observed in gastric carcinoma tissue.…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…Recently, we have pointed out that the expression of CARP is significantly decreased in lung cancer tissues, suggesting that decreased expression of CARP might be associated with tumorigenesis of lung cancer [10]. In the present study, a similar tendency in the change of CARP expression was observed in gastric carcinoma tissue.…”
Section: Discussionsupporting
confidence: 86%
“…It has been reported that JAB1 promotes cell proliferation by directly binding to p27, and induces nuclear export and subsequent degradation of p27 [27], [28]. We have demonstrated that CARP repressed JAB1-mediated AP-1 activation and enhanced p27 nuclei accumulation [10]. JAB1 induces p53 cytoplasmic localization and its subsequent degradation, which helps to maintain low levels of p53 under normal conditions [26], [29], [30].…”
Section: Discussionmentioning
confidence: 65%
See 3 more Smart Citations